Problematics and Strategies of Islamic Education Teachers in Utilizing Projector Media to Enhance Fiqh Learning in the Digital Era - MUH. Akbar Mahdi Supriyanto; Jailani Jailani; Zainur Rayhan Dinollah; Zhakyatur Rahman (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
The advancement of digital technology has increasingly promoted the incorporation of technology-based learning media into educational settings, including Islamic Religious Education. This study seeks to investigate the use of projectors in Fiqh instruction, identify the strategies employed by teachers to combine video-assisted learning with practical teaching activities, and examine the contribution of school facilities in facilitating technology-supported learning at MTs Raudlatul Muta'allimin, Pamekasan. This study used a qualitative descriptive method and focused on a case study approach. Data collection included watching classes, talking closely with Fiqh teachers and the school principal, and looking at important documents. The analysis of the gathered data was conducted using the interactive model proposed by Miles and Huberman, which includes data condensation, data presentation, and verification of conclusions. The findings suggest that the implementation of projectors in learning significantly enhances the effectiveness of Fiqh instruction by providing audiovisual representations of religious practices, leading to improved students' comprehension and participation. By showcasing instructional videos before practical exercises, students can gain firsthand knowledge of the correct procedures and use them for independent study. In addition, students were pleased with the use of projectors, citing their increased involvement and focus on learning during lessons. Furthermore, the research indicated that adequate facilities, supportive school policies, and teachers' willingness to embrace technology are essential for maximizing the benefits of projector-based learning. The results indicate that the use of audiovisual media and hands-on learning activities can enhance the effectiveness of Fiqh instruction and facilitate technology-based education in Islamic schools.